The structured assessment of violence risk in youth in a large community sample of young adult males and females: The TRAILS study - Sijtsema, Jelle J.; Kretschmer, Tina; Van Os, Titus (Psychological Assessment, 2015)
This study examined associations between the Structured Assessment of Violence Risk in Youth (SAVRY; Borum, Bartel, & Forth, 2002) risk and protective items, identified clusters of SAVRY items, and used these clusters to predict police contact and violence. SAVRY items were assessed in a community sample of adolescent boys and girls (N = 963, 46.5% boys) via self-, parent, and teacher reports at ages 11 and 13.5 as part of a longitudinal cohort study. Police contact and violence were assessed at age 19. Correlations between risk and protective items and police contact and violence were largely similar in boys and girls, though there were some differences with regard to outcome measure. Principal factor analysis on the SAVRY items yielded a 2-factor model, distinguishing between History of Violence/Dysregulation and Social Support factors. Follow-up analyses showed incremental validity of the Social Support factor over and beyond the History of Violence/Dysregulation factor and sex in the prediction of violence. The findings provide new insights into the SAVRY factor structure and show that the SAVRY was able to predict violence in a community sample of adolescents over a period of 4 to 7 years.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Adolescence; Assessment; Delinquency; Risk; SAVRY